The strength properties of paper from Hura crepitans according to 15%, 20% and 25% active alkali using kraft pulping / Mohamad Sabri Md Zulkifle - Md Zulkifle, Mohamad Sabri (2004)
This research was done on Payung Indonesia (Hura Crepitans) to study the strength properties of paper and suitability using chemical pulping. The method that has been used to produce paper by using Kraft pulping with different percentages of active alkali. The percentages that we use are 15%, 20% and 25% with 2000 r.p.m. beating process. The testing done under the TAPPI standard to determine the paper properties. The conclusion that we get from this research is, the yield is decrease to 16.73% after we produce the pulp yield. The freeness result also decreases to 13.16%. It goes the to the tearing index, folding endurance and burst index, all of these decreases to 16.27%, 68.136% and 23.61%. The only testing the increase is the tensile index. This proves that the different percentages of active alkali will give different affect to the strength properties of the paper. The beating process also plays an important role of the strength properties of the paper that we produce.